Transcutaneous auricular vagus nerve stimulation modulates masseter muscle activity, pain perception, and anxiety levels in university students: a double-blind, randomized, controlled clinical trial - Ferreira, Luciano Maia Alves; Brites, Ricardo; Fraião, Gonçalo; Pereira, Gonçalo; Fernandes, Henrique; de Brito, José Américo Almeida; Pereira Generoso, Laura; Maziero Capello, Maria Gabriela; Pereira, Gabrielly Santos; Scoz, Robson Dias; Silva, Josie Resende Torres; Silva, Marcelo Lourenço (Frontiers in Integrative Neuroscience, 2024)
Introduction Chronic anxiety is a statemarked by sustained activation of the masseter muscle, manifesting in both mental and physical strain. This prolonged tension can significantly impact mental wellbeing and cognitive abilities, posing a risk for a range of health complications. This double-blind, randomized, controlled clinical trial investigated the impact of transcutaneous auricular vagus nerve stimulation (TAVNS) on masseter muscle activity, pressure pain threshold (PPT), and anxiety levels in university students with elevated anxiety. Methods Forty-two participants meeting inclusion criteria were randomly assigned to either active TAVNS or sham TAVNS groups. Various parameters, including masseter muscle electromyographic (EMG) signals, PPT, and Beck Anxiety Inventory (BAI) scores, were assessed before pretreatment, immediately after the intervention week, and 2 weeks follow-up. Results Active TAVNS significantly reduced both left and right masseter activation during resting mandibular position, persisting for 2 weeks post-intervention. Additionally, TAVNS induced a lasting decrease in both left and right masseter PPT, indicative of altered pain perception. Notably, BAI scores showed a substantial reduction, emphasizing TAVNS as a potential intervention for anxiety, with effects maintained at the 2-week follow-up. Discussion This study provides comprehensive insights into the multifaceted effects of TAVNS on physiological and psychological aspects associated with anxiety in university students. The promising results underscore TAVNS as a potential neuromodulatory intervention for anxiety-related conditions, warranting further research and clinical exploration. Clinical Trial Registration https://ensaiosclinicos.gov.br/rg/RBR-4s4kt2r.